Sample preparation handbook for tranmission electron microscopy. techniques - Ayache, Jeanne; Ayache, Jeanne, 1951- (New York : Springer, 2010)
This two-volume Handbook is a comprehensive guide to sample preparation for the transmission electron microscope. Sample Preparation Handbook for Transmission Electron Microscopy: Volume 2: Techniques describes 14 different preparation techniques, including 22 detailed protocols for preparing thin slices for TEM analysis. Compatibility and pre-treatments are also discussed. Experimental conditions and guidelines, options and variations, advantages and constraints, technical hints from the authors years of experience, common artifacts, and theoretical issues are all considered. Particular attention is given to the type of material, conditioning, compatible analysis of a given preparation, and risks. This practical and authoritative reference companion deserves a place on the bench in every TEM lab. Key Features of the Handbook:Combines all of the latest techniques for the preparation of mineral to biological samples Compares techniques in terms of their application areas, limitations, artifacts, and types of analysis (macroscopic, atomic, or molecular level)Describes physical characteristics, chemistry, structure/texture, and orientation properties of materials in relation to the most appropriate type of TEM analysis Links to a complementary interactive database website which is available to scientists worldwide*Written by authors with 100 years of combined experience in electron
Introduction.- Preliminary preparation techniques.- Thinning preparation techniques.- Mechanical preparation techniques.- Replica techniques.- Techniques specific to fine particles.- Contrast-enhancement and labeling techniques.-
Includes bibliographical references and index.
1
Keywords: Electron microscopy; Material Science; Nanotechnology